PENINGKATAN KOMUNIKASI DAN HASIL BELAJAR MATEMATIKA MELALUI MODEL PEMBELAJARAN KOOPERATIF THINK PAIR SHARE PADA SISWA KELAS III SDN 003 SUNGAI KUNJANG TAHUN PEMBELAJARAN 2016/2017 - Samsul Adianto (PENDAS MAHAKAM: Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2018)
ABSTRACTThis research is for class action to purpose increase of communication and result learning mathematical by Cooperative Think Pair Share. For third grade SDN 003 Sungai Kunjang. This research do in SDN 003 Sungai Kunjang by subject research is communication and result learning mathematical by Cooperative Think Pair Share. The research do as many as two times cycle. Each cycle do two times meeting. The technical is collecting data use paper observation and test. The result of data is present on narrative, average, and present-ace. Whereas the observatory is researcher. From result analysis that got student communication group has experienced increased from cycle I until II, cycle I (48.73%) cycle II (94%) and personally communication on cycle I has (26.31%), cycle II has (80.48%). The learning completeness student has increased form cycle I until II that is cycle I (45.83%) cycle II (92%). Based on the research that can concluded by learning Cooperative Think Pair Share that can increase communication and result learning mathematical Third grade SDN 003 Sungai Kunjang.Key Word:  Communication, Result Learning, and Cooperative TPS